2017
DOI: 10.2215/cjn.11491116
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Kidney Disease

Abstract: Diabetic kidney disease develops in approximately 40% of patients who are diabetic and is the leading cause of CKD worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
786
2
22

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,859 publications
(971 citation statements)
references
References 75 publications
10
786
2
22
Order By: Relevance
“…Podocytes decreased in frequency by >10-fold in diabetic mice (to 12 out of 14,837 total cells, 0.08%), consistent with previous reports that podocytes are one of the earliest cell types to be damaged and lost in DKD ( Fig. 3C) [39][40][41] . HyPRseq also detected an increase in thick ascending limb/distal convoluted tubule (TAL/DCT) cells and a decrease in endothelial cells, in agreement with early changes observed in DKD ( Fig.…”
Section: Measuring Cell Type Frequencies and Low-abundance Genes In Tsupporting
confidence: 91%
“…Podocytes decreased in frequency by >10-fold in diabetic mice (to 12 out of 14,837 total cells, 0.08%), consistent with previous reports that podocytes are one of the earliest cell types to be damaged and lost in DKD ( Fig. 3C) [39][40][41] . HyPRseq also detected an increase in thick ascending limb/distal convoluted tubule (TAL/DCT) cells and a decrease in endothelial cells, in agreement with early changes observed in DKD ( Fig.…”
Section: Measuring Cell Type Frequencies and Low-abundance Genes In Tsupporting
confidence: 91%
“…1 Metabolic alterations associated with diabetes lead to renal pathologic changes including tubulointerstitial inflammation and fibrosis, glomerular hypertrophy, and glomerulosclerosis. 1 However, because only less than 10% of patients with diabetes ultimately reach end-stage renal disease, there must be something missing in our understanding of the pathophysiology of DKD. Genetic studies have not identified a major genetic contribution, 2,3 although it is likely that there are important genetic determinants.…”
mentioning
confidence: 99%
“…These risk factors can be classified as those relating to susceptibility, initiation, and progression. The following factors are considered to influence progression: ethnicity; systemic conditions, including control of hyperglycemia, overweight, and hypertension; factors leading to acute kidney injury (AKI); and high protein intake (15). However, these risk factors cannot completely explain the rapid progression of DKD in the current study cohort.…”
Section: Discussionmentioning
confidence: 92%